Bibliometric analysis and science mapping of global scientific publications on technical vocational education training (TVET) - Abd Majid M.Z.; Kasavan S.; Siron R. (Emerald Publishing, 2025)
Purpose: While technical vocational education training (TVET) has been studied in-depth, the evolution and performance patterns of the subject remain unknown and limited. A bibliometric analysis was performed to examine the global scientific literature to assess the state of the art in TVET research over the past 23years. Design/methodology/approach: The Web of Science (WoS) database was searched to explore TVET-related research from 1999 to 2021, resulting in the identification of 7,512 articles. The VOSviewer software was used to investigate the network of collaboration between authors, institutions, countries and author keywords. Findings: The results reveal that the subject categories of ?education? and ?educational research? are the most prolific contributors to TVET-related research, with 3,314 articles. Most of the previous studies in Phase I (1999?2006) focussed on human capital resources development in the TVET sector. Phase II (2007?2014) follows with the centralisation of TVET, focussing on technology transition in education. However, in Phase III (2015?2021), researchers appear to focus on vocational studies in higher education towards increasing the productivity of human resources via the implementation of technology transition. Originality/value: The valuable findings of this study can facilitate better understanding among scholars on the trends of TVET research developments and on the direction of future research. ? 2022, Emerald Publishing Limited.